LGG-36. IMPACT OF BRAFv600e MUTATION 7q34 DUPLICATION AND CDKN2A DELETION IN A MONOCENTRIC COHORT OF 86 PEDIATRIC LOW GRADE GLIOMAS (PLGG). Issue 2 (22nd June 2018) - Lhermitte, Benoit; Guerin, Eric; Legrain, Michelle; Arca, Marc; Coutant, Marie; Sebastia, Consuelo; Douzal, Valérie; Gabor, Flaviu; Entz-Werlé, Natacha
Abstract: The main diagnosis in pediatric brain tumor setting is PLGG, where BRAF is the more recurrent gene deregulated in those tumors (e.g. mutation v600e or 7q34 duplication). The molecular research of such abnormalities is performed now routinely for a diagnostic purpose. Recently, few publications were highlighting differently the impact of BRAF rearrangements and CDKN2A deletion, as independent prognostic factors linked to a worst outcome. Therefore, we were looking to our monocentric cohort of PLGG. Among 185 PLGGs diagnosed during the 10 last years, 86 were surgically resected or biopsied and diagnosed as a pilocytic astrocytoma or ganglioglioma. The molecular diagnosis was performed in all those PLGGs. The BRAF v600e mutation was detected by immunohistochemistry and confirmed by NGS (Next Generation Sequencing) analysis and the 7q34 duplication was assessed by reverse transcription polymerase chain reaction-based sequencing. We also detected the CDKN2A deletion by our NGS technique. 12 out of 86 tumors were bearing the BRAF mutation and 66 had a BRAF-KIAA1549 fusion transcript. Six patients with a BRAF mutation were relapsing after first line treatment and only one had a concomitant CDKN2A deletion and died rapidly. Among the tumors with a 7q34 duplication, one third (22) were relapsing and 2 were bearing also a CDKN2A deletion. All patients with this deletion died after first relapse or rapidly after diagnosis. No correlation was observed between those molecular abnormalities and the age of patients, whereas quantitative MRI parameters were significantly linked to the molecular diagnosis.